Clinical outcomes of otitis media with effusion following palatoplasty in patients with incomplete cleft palate. (2nd January 2019) - Jin, Lei; Li, Keyong; Li, Xiaoyan
Abstract: Background: Diagnosis and treatment strategies for CP with OME and the timing of ear tube insertion remain controversial. Objectives: To analyze the clinical outcomes of otitis media with effusion in children with incomplete cleft palate after palatoplasty prospectively. Methods: A total of 30 children (10 months–2 years old) with incomplete CP were enrolled in this study and received at least 6 months of follow-up evaluations after palatoplasty. Results: The overall improvement rate of OME was as high as 26% in this group. Average air conduction hearing threshold was significantly better than that before surgery in the 8 patients with improved OME ( p < .05). Among the 8 children with improved OME, 7 (87.5%) were found to have middle ear effusion that improved within 6 months after CP repair. There was no significant difference in the improvement rate between the severe degree II group and the mild group. Conclusion: A 6-month follow-up period is recommended. The severity of incomplete CP is not fully related to the function of the eustachian tube. Significance: The overall improvement rate was as high as 26%, and effusion in the tympanic cavity subsided in 7 out of 8 cases within 6 months after the CP repair.